Le concept de traumatisme en psychanalyse - Thierry Bokanowski (Sillages Critiques)
A paper by a psychoanalyst, specialized in trauma, both clinically and theoretically, that strives at giving a scientific yet accessible medical definition and retraces the history of the concept inside the field of psychoanalysis, with special reference to Freud and Ferenczi, but also to more recent researchers.